Experimental characterization and validation by FEM analyses of a 3D-printed support. Issue 1 (February 2021) - Cosmi, F; Dal Maso, A
Abstract: Devices for training of healthcare specialists are widespread applications of 3D printing. BES TEST™ is an innovative test for the diagnosis of osteoporosis and similar bone diseases, based on mechanical simulations performed on a virtual biopsy of the patient's fingers, obtained by radiograms. Operator training is performed on a phantom hand, which is held in place by a specifically-designed support, which was 3D printed using stereolithography (SLA) with Formlabs Tough V5™ resin. Our aim is twofold: (1) perform a mechanical characterization of the resin and (2) verify that the obtained material characteristics can be used for the design of 3D-printed parts, in particular the phantom hand support. Tensile tests were performed following ISO-527. FEM analyses were carried out on the support CAD model adopting the experimentally-obtained material properties. The calculated displacements were compared with those measured experimentally on the prototype, which was manufactured using the same 3D printing and post-curing parameters as the tensile samples. FEM and experimental results were in very good agreement (error < 5.5%): this confirms that, when studying the mechanical performance of SLA 3D-printed parts, it is good practice to characterize the resin using the same printing and post-curing parameters as the final part.